Literature and Cinema: Aspects of Interaction - Kuryaev, Ilgam Ryasimovich; Osmukhina, Olga Yurievna (Journal of History Culture and Art Research, 2018)
The article is devoted to understanding the interaction of literature and cinema. It outlines the key approaches to studying this interaction: First, the study of the specifics of the participation of cinematographic interpretation in the formation of literary history and the history of reading; secondly, the definition of the degree of mutual influence of literature and cinematography. The problem of intermedia, which actualizes the mutual influence of the two arts, is connected with the search for new ways of influence, the translation of one text into the coordinates of the other. Literature is looking for new ways of unfolding the plot, building text space, cinematography - new ways of interpreting the stories and developing a verbal layer of cine-text. The theme of their mutual influence became an object of close observation and analysis both among the classics of Soviet literary criticism and cinematography, and among Western theoreticians of the cine-text; research in this area has now of great importance and undoubted interest. At the same time, it is interesting that the greatest surge of purely scientific interest in cinematography occurs in the 1920-30s and the end of the 20th century. And this is due to the approval and the prevalence of cinema (more widely - audiovisual entertainment content) in the public space amid large historical changes. Cinema becomes a way of transformation, of reorganization of the perception of a person, of his way, by the method of familiarizing the individual with a large cultural layer of the country. Through screenings, the cinema not only indirectly acquaints a person with the texts of literary classics, but also participates in the development of the literary text itself, preventing its “necrosis”. Literature is becoming more and more “pictorial”, palpable for the reader. At the same time, it should be said that neither the theory of cinema nor literary criticism has developed a scientific analysis apparatus that contributed to the competent and objective analysis and comparison of two texts, literary and cinematographic. Thus, there is a task in developing methodological grounds for comparing the screen version of literary works and their primary sources, as well as determining the degree of mutual influence of literature and cinema.